Computational Screening of Repurposed Drugs Targeting Sars-Cov-2 Main Protease By Molecular Docking - Yin, Yow Hui; Yin-Quan, Tang (Sudan Journal of Medical Sciences, 2022)
Background: COVID-19 (Coronavirus disease 2019) is caused by the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), which poses significant global health and economic crisis that urges effective treatment. Methods: A total of 11 molecules (baricitinib, danoprevir, dexamethasone, hydroxychloroquine, ivermectin, lopinavir, methylprednisolone, remdesivir, ritonavir and saridegib, ascorbic acid, and cepharanthine) were selected for molecular docking studies using AutoDock VINA to study their antiviral activities via targeting SARS-CoV’s main protease (Mpro), a cysteine protease that mediates the maturation cleavage of polyproteins during virus replication. Results: Three drugs showed stronger binding affinity toward Mpro than N3 (active Mpro inhibitor as control): danoprevir (–7.7 kcal/mol), remdesivir (–8.1 kcal/mol), and saridegib (–7.8 kcal/mol). Two primary conventional hydrogen bonds were identified in the danoprevir-Mpro complex at GlyA:143 and GlnA:189, whereas the residue GluA:166 formed a carbon–hydrogen bond. Seven main conventional hydrogen bonds were identified in the remdesivir at AsnA:142, SerA:144, CysA:145, HisA:163, GluA:166, and GlnA:189, whereas two carbon–hydrogen bonds were formed by the residues HisA:41 and MetA:165. Cepharanthine showed a better binding affinity toward Mpro (–7.9 kcal/mol) than ascorbic acid (–5.4 kcal/mol). Four carbon–hydrogen bonds were formed in the cepharanthine-Mpro complex at HisA:164, ProA;168, GlnA;189, and ThrA:190. Conclusion: The findings of this study propose that these drugs are potentially inhibiting the SAR-CoV-2 virus by targeting the Mpro protein.